Pengaruh Beban Kerja dan Pembagian Kerja dalam Perspektif Gender terhadap Efektivitas Pemajangan Produk pada Etalase di Toko Budi Snack Tasikmalaya - Deliana Sulistia Sari; Ani Wahyu Rachmawati (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study was motivated by retail operational issues related to low product display effectiveness (on-shelf availability) at Budi Snack Store in Tasikmalaya, characterized by high rates of product shortages on the shelves during peak hours, delays in restocking, and suboptimal shelf arrangement. These issues were analyzed through the factors of workload and division of labor, while also examining the implications of gender perspectives in the distribution of store operational tasks. This study aims to identify and analyze the characteristics of workload, division of labor, and product display effectiveness, both individually and simultaneously. The approach used was a quantitative approach employing descriptive and verifiable methods. The unit of analysis consisted of 42 operational employees at Toko Budi Snack in Tasikmalaya, using saturated sampling (census). Primary data were collected through a Likert-scale questionnaire, while secondary data were obtained from field observations and a literature review. Data analysis techniques included descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, the coefficient of determination, and hypothesis testing using the partial (t) test and the simultaneous (F) test. The results of this study are expected to provide theoretical and empirical insights into the influence of workload pressure and clarity of task division—as they intersect with gender dynamics—on the effectiveness of product display in the snack food retail sector.